Fluido no Newtoniano para chalecos antibalas - Pliego, G. del; Pérez, A.; Rodríguez, L.; Sánchez, P. (Ingenia Materiales, 2022)
Our experiment consists of analyzing a non-Newtonian fluid, testing it at different pressures and thus seeing its peculiar behaviour.A non-Newtonian fluid is a curious material whose viscosity changes with temperature and the stress applied to it at a given time. As a result, you will never be able to have a defined and constant viscosity value.That is, if we introduce an object at low speed, we will go through it without difficulty as if it were a liquid, since we do not exert enough pressure for its atoms to rearrange.In contrast, when a non-Newtonian fluid is struck, the incoming applied force causes it to temporarily behave like a solid.